Anotaciones sobre el uso de las formas el y este / ese / aquel como femeninos - Bravo García, Eva María (ELUA: Estudios de Lingüística. Universidad de Alicante, 1990)
The essay is about the use of the forms el y este / ese / aquel before nouns and adjectives which begin with stressed /a-/. General approach to this problem appears included in the Academic Grammar very clearly, but varieties in different speak levels are frequent. Author, starting from a survey between university students, shows us how, in spite of the knowledge that they have, there are sintagmatic combinations which express important doubts, so in may people the confusion is considerably high, this fact involves that the Norm isn't placed on speaker's mind, it can produce confusions and changes on gender's use.